Linear algebra and group theory - Smirnov, V. I. (Vladimir Ivanovich) 1887-1974 (Dover books on mathematics., 2011)
"Derived from an encyclopedic six-volume survey, this accessible text by a prominent Soviet mathematician offers a concrete approach, with an emphasis on applications. Containing material not otherwise available to English-language readers, the three-part treatment covers determinants and systems of equations, matrix theory, and group theory. Problem sets, with hints and answers, conclude each chapter. 1961 edition"--Provided by publisher.